Upregulation of Prickle2 Ameliorates Alzheimer’s Disease-Like Pathology in a Transgenic Mouse Model of Alzheimer’s Disease - Sun, Fengxian; Jiang, Fang; Zhang, Na; Li, Hua; Tian, Weiping; Liu, Weiying (Frontiers in Cell and Developmental Biology, 2020)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder that has no effective therapies. Prickle planar cell polarity protein 2 (Prickle2), is an important cytoplasmic regulator of Wnt/PCP signalling. It has been reported that Prickle2 deficiency reduced neurite outgrowth levels in mouse N2a cells and led to autism-like behaviours and hippocampal synaptic dysfunction in mice. However, much less is known about the relationship of Prickle2 to AD pathogenesis. RT-qPCR, Western blot and IHC results showed that the mRNA and protein levels of Prickle2 were reduced in amyloid precursor protein (APP)/PS1 mice. Intracerebral injection of Prickle2-overexpressing AAV9 vectors improved the cognitive deficits in APP/PS1 mice. We also demonstrated that Prickle2 could repress oxidative stress and neuroinflammation, ameliorate the amyloid β (Aβ) plaque pathology and reduce Tau hyperphosphorylation in APP/PS1 mice. Further investigation of the mechanism of Prickle2 in AD revealed that Prickle2 inhibited Wnt/PCP/JNK pathway in vivo and in vitro. The downregulation of GATA2 induced the silencing of Prickle2 by binding its promoter region. Our results suggest that Prickle2 might be a potential candidate for the diagnosis and treatment of AD.